Molecular biology - McLennan, Alexander G. (BIOS instant notes series, 2013)
"Instant Notes in Molecular Biology, Fourth Edition is the perfect text for undergraduates looking for a concise introduction to the subject, or a study guide to use before examinations. Each topic begins with a summary of essential facts, an ideal revision checklist followed by a description of the subject that focuses on core information, with clear, simple diagrams that are easy for students to understand and recall in essays and exams" -- Provided by publisher